1995
DOI: 10.1111/j.1541-0064.1995.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

International Migration and Remittances to a Lebanese Village

Abstract: "A number of hypotheses concerning remittances from foreign emigrants are developed and tested using questionnaire survey data from Lala, a Lebanese village. According to the theory, a rural family engages in an implicit insurance-type contract with the potential migrant because both are averse to risk.... Results from testing the hypotheses are somewhat consistent with the proposition that, after a period of adjustment, migrants do begin to remit, thereby providing their families with an insurance against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Time since migration shows a significant non‐linear effect on the propensity to remit. This finding is consistent with literature detecting an inverted‐U shape (Lucas and Stark, ; Amery and Anderson, ; de la Brière et al., ; Cai, ; Liu and Reilly, ; Amuedo‐Dorantes and Pozo, ; Craciun, ; Dustmann and Mestres, ). Time, however, is not significant in the beta part of the model, suggesting that the decision of how much to remit is independent of the length of stay in Italy.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Time since migration shows a significant non‐linear effect on the propensity to remit. This finding is consistent with literature detecting an inverted‐U shape (Lucas and Stark, ; Amery and Anderson, ; de la Brière et al., ; Cai, ; Liu and Reilly, ; Amuedo‐Dorantes and Pozo, ; Craciun, ; Dustmann and Mestres, ). Time, however, is not significant in the beta part of the model, suggesting that the decision of how much to remit is independent of the length of stay in Italy.…”
Section: Resultssupporting
confidence: 92%
“…A number of scholars have argued that the relationship between the length of stay in the receiving country and remittance behaviours is not linear, but has rather an inverted‐U shape (Lucas and Stark, ; Amery and Anderson, ; de la Brière et al., ; Cai, ; Liu and Reilly, ; Amuedo‐Dorantes and Pozo, ; Craciun, ; Dustmann and Mestres, ). During their early phase after arrival, remittances are low due to social and economic integration difficulties, precarious and low‐paid jobs, and low savings (Todisco, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…First, at the micro level, the issue of who sends (or does not send) remittances to whom has moral dimensions, and can be a delicate aspect of interpersonal transnational relationships (Carling 2008b). The experiences of Amery and Anderson (1995) in rural Lebanon illustrate this point. They interviewed household heads and initially enquired about the level of remittances received from each migrant son.…”
Section: Sensitivity and Biasmentioning
confidence: 97%
“…Researchers (e.g. Amery and Anderson, 1995;Carling, 2008) have found that in the specific context of migrants sending remittances in cash or kind, the relationship between the giver and receiver is central as it is a determinant of the giver's motives. It is conceivable that a heightened need to sustain relationships and other more practical interests may contribute to this finding.…”
Section: Relationship Between the Giver And The Recipientmentioning
confidence: 99%
“…Reciprocity is consistently identified as a motive for giving gifts in cash or kind by migrants to those in their home countries (e.g. Amery and Anderson, 1995;Khatib and Pezdir, 2009). Campbell's (2009) review suggests that migrants remit money and gifts to reciprocate kindness and the support provided by family and friends during the initial stages of migration.…”
Section: Maintaining Rituals and Customsmentioning
confidence: 99%